Drowning in the Eastern Mediterranean region: a systematic literature review of the epidemiology, risk factors and strategies for prevention - Amy E. Peden; Ali Işın (BMC Public Health, 2022)
Abstract Introduction Globally, drowning is a significant cause of preventable mortality and morbidity. The Eastern Mediterranean region (EMR) comprises 22 countries of extreme disparity in income and is a region impacted by conflict and migration. We systematically review literature published on drowning in the EMR. Methods Peer-reviewed literature (limited to original research) was identified using Embase, PubMed, Scopus, SportsDiscus, and Web of Science databases. Literature was independently dual screened at title/abstract and full text stages with dual data extraction (20% of included studies). Studies were included if they reported epidemiology, risk/protective factors and/or prevention strategies for drowning (unintentional and intentional; fatal and non-fatal) of residents, tourists or migrants in the EMR. Literature was assessed against the [Australian] National Health and Medical Research Council’s Levels of Evidence. Results Seventy-two studies were included in this review (epidemiology 68 studies; risk/protective factor 13 studies; prevention strategies 19 studies). Iran (n = 27), Saudia Arabia (n = 11) and Pakistan (n = 10) recorded the largest number of dedicated studies. Studies predominately focused on unintentional drowning. Ninety-two percent of included studies (n = 66) were ranked as being low evidence (level IV). The majority of studies explored drowning among children and adolescents (0–19 years). All-age fatal drowning rates varied from a low of 0.48 per 100,000 (United Arab Emirates; 2002; Ministry of Health death registry data) to a high of 18.5 per 100,000 (Egypt; 2014–15; WHO mortality database). Commonly identified risk factors included being male, young age, submersion time and resident status. Common prevention strategies public education, lifeguard supervision, and cardiopulmonary resuscitation. Discussion Gaps in understanding of drowning burden in some countries within the region, as well as region-wide risk factor identification for adult drowning, intentional and migration-related drowning, impair the ability of nations to advance drowning prevention. There is a need for investment in implementation and evaluation of drowning prevention interventions in the EMR. Conclusion Drowning is a significant cause of mortality and morbidity in the EMR. The recent UN declaration on global drowning prevention may provide the impetus to invest in drowning prevention research, policy, and advocacy with the aim of reducing drowning-related harms in the EMR. Trial registration Registration number: # CRD42021271215 .